Are changes in the wnt/b-catenin pathway involved in cocaine and stress-induced long-term neuroadaptations? - Cuesta, Santiago (2017)
Drug addiction has been defined as a chronic relapsing brain disease, characterized by compulsive drug seeking and use, despite harmful consequences. This phenomenon has been extensively studied and the use of animal models has contributed to elucidate neurobiological bases of the different stages in the addiction process. For the past years, we have been studying the role of the Wnt (Wingless-related integration site) pathways in cocaine-induce neuroadaptations by using the behavioral sensitization paradigm to model addiction-like behaviors. The Wnt pathways are critical during the development of both the central and peripheral nervous systems. In particular, we centered our attention on the Wnt/β-catenin or canonical pathway. This pathway mediates the stabilization and nuclear translocation of the final effector β-catenin, where it can promote the expression of different target genes. Our findings reveal a specific spatiotemporal participation of the Wnt/β-catenin pathway in cocaine-induced behavioral sensitization. We found that while the initiation or development of sensitization involves an inhibition in the Prefrontal Cortex?s canonical pathway, the expression is related with activation in the Nucleus Accumbens. Furthermore, we recently discover that stress during adolescence has an impact on cocaine-induced effect in adulthood. Intriguingly, we also found that the exposure to this early life stress influence the activity of the Wnt/β-catenin pathway, proposing that this signaling pathway could be mediating the proactive effect of stress on drug properties. In this manuscript, we cover different mechanisms that may underlie cocaine- and stress-induced changes in the Wnt canonical pathway. We also revise the idea of this pathway as a common target for adolescent stress and for the vulnerability to drug abuse later in life. We suggest that the canonical Wnt pathway constitutes a promising target that may open a door to new therapeutic strategies for the treatment of cocaine addiction.